Assyrian Nimrud and the Phoenicians. Issue 1 (24th October 2013) - Herrmann, Georgina; Laidlaw, Stuart
Abstract : The first ivories at the Assyrian imperial capital of Kalhu/Nimrud in northern Iraq were found by Henry Layard in the mid-19th century. Max Mallowan and David Oates (both professors at the Institute of Archaeology), together with the British School of Archaeology in Iraq, worked there from 1949–1963 and found literally thousands more, both in the palaces of the acropolis and in a large outlying building known as Fort Shalmaneser. During the last 50 years the majority has been published in the Ivories from Nimrud series, so that it is now possible to look at this remarkable corpus as a whole. It immediately becomes evident that most were not made in Assyria, but imported from the states conquered by the Assyrian kings in the early 1st millennium BC. Many show a debt to the art of Egypt and can be assigned to the 'Phoenician tradition', thus recording the otherwise little-known art of the Phoenicians, long famed as master craftsmen. 'Syrian-Intermediate' ivories are versions of Phoenician ivories and may represent the art of the recently-arrived Aramaean kingdoms, while the very different 'North Syrian' ivories derive from earlier Hittite traditions.